Building A Community Mindset for The Advancement of The Local Wisdom Economy by Utilizing Technology - Hasibuan, Rapotan; Siregar, Ari Anshari; Rizti, Muthia; Safithry, Cindy Yunika (Jurnal Abdi Mas Adzkia, 2023)
Building a community mindset is very important, especially to improve the economy. It is known that poverty is the biggest challenge for society, and this problem needs to be resolved. This can happen because the community's mindset is behind technology development, where people only use technology for things that could be more useful. Therefore, it is necessary to change people's views on the use of technology, especially since technological advances are currently inseparable from people's lives. This technological advancement has caused enormous changes in the life of humanity with all its civilizations and cultures. This change also greatly impacts the economy as long as it can utilize it properly. However, many people still need to learn how to utilize technological developments to improve the economy of individuals and even regions. Therefore, it is necessary to guide the community to be wiser in using technology, which will be very beneficial for the community's survival and even the economic progress of the community, especially since the community can introduce local wisdom to the world.  Keywords: Economy, Local Wisdom, Society, Technology